1960
DOI: 10.2134/agronj1960.00021962005200030013x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Anatomical, and Histochemical Studies on the Navy Bean Seed1

Abstract: Synopsis The seed coats, cotyledons, and embryonic axes constituted 7.7%, 90.5%, and 1.8% of the dry bean matter, respectively. Significant differences were found in the chemical composition of seed tissues. The migration of water through hydrated seed coats was demonstrated. The starch content of cotyledons was 39.3%. Starch granules were imbedded in protein matrices of parenchyma cells. The parenchyma cells of cotyledons possessed thick secondary walls with numerous paired pits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Eventually, the entire seed imbibed water. Migration of water has been demonstrated through hydrated seed coats of navy bean (19). This gradual water uptake by SHS is in agreement with reports on the kinetics of water uptake by seeds of other leguminous species (3,26).…”
Section: Resultssupporting
confidence: 90%
“…Eventually, the entire seed imbibed water. Migration of water has been demonstrated through hydrated seed coats of navy bean (19). This gradual water uptake by SHS is in agreement with reports on the kinetics of water uptake by seeds of other leguminous species (3,26).…”
Section: Resultssupporting
confidence: 90%
“…This increase correlates well with the elevated moisture content (r = 0.972, P < 0.0001). It is logical to assume that the increase in hardness of the raw bean is related to the intracellular components, of which starch is the primary constituent, comprising approximately 40% of the cotyledons on a dry weight basis (Powrie, Adams and Pflug, 1960). It is believed that the initialS-tO% of water absorbed by starch is 'bound water' and that further hydration upon equilibration in a saturated atmosphere causes expansion, the degree of which is dependent upon the source of the starch (Leach, 1965).…”
Section: Effect Of Soaking Time On Hardnessmentioning
confidence: 99%
“…Several studies have indicated a possible relationship between seed microstructure and water absorption in legume seeds (Coe and Martin, 1920;Watson, 1948;Snyder, 1936;Powrie et al, 1960;Saio, 1976;Sefa-Dedeh and Stanley, 1979). However, the precise role of microstructural constituents of the seed in water absorption is still not known.…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise role of microstructural constituents of the seed in water absorption is still not known. The seed coat (Coe and Martin, 1920;Powrie et al, 1960;Sefa-Dedeh and Stanley, 1979), hilum (Hyde, 1954), and micropyle (Snyder, 1936;Kyle and Randall, 1964) have individually been related to the permeability of legume seeds. Recently, Sefa-Dedeh and Stanley (1979) suggested that all three constituents (the seed coat, hilum, and micropyle) together may form an integral water absorption/removal system.…”
Section: Introductionmentioning
confidence: 99%